2015
DOI: 10.1097/dad.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Actinic Keratosis, Transected

Abstract: Evaluation of superficial transected shave biopsies of squamous neoplasms often presents a diagnostic dilemma for the dermatopathologist because of the lack of complete visualization of the base of the epidermis. Fear of "missing" an invasive carcinoma must be balanced with avoidance of overdiagnosis of precancerous actinic keratosis (AK), especially on cosmetically sensitive areas such as the face. If a concern exists that a more invasive component may be present, a diagnosis of AK transected at the base (AKT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Due to the clinical heterogeneity, the pre‐malignant lesions AK and BD are often challenging to differentiate from cSCC leading clinicians to biopsy or excise lesions that may not be cSCC 7,8 . Recent data on the prevalence of clinical misdiagnosis in AK and BD are unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the clinical heterogeneity, the pre‐malignant lesions AK and BD are often challenging to differentiate from cSCC leading clinicians to biopsy or excise lesions that may not be cSCC 7,8 . Recent data on the prevalence of clinical misdiagnosis in AK and BD are unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the clinical and histopathological heterogeneity, it is sometimes difficult to differentiate premalignant AK and BD lesions from cSCCs resulting in undertreatment, overtreatment, and sometimes the excision of benign lesions. [7][8][9] In this study, we reported the identification of nine and one proteins that could non-invasively differentiate cSCC from AK and BD lesions, respectively. Two proteins including S100A12 and SPRR1A were found to differentiate between BD and AK lesions.…”
Section: Proteomic Analysis Identifies Non-invasive Protein Signature...mentioning
confidence: 96%
See 1 more Smart Citation